2019
DOI: 10.1155/2019/1390358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Commercial Fertilizers, Harvest Date, and Storage Time on Two Organically Grown Blackberry Cultivars: Physicochemical Properties, Antioxidant Properties, and Sugar Profiles

Abstract: Despite increased consumer interest in organic produce, little is known about how different organic production methods affect both the traditional measures of quality and the naturally occurring health promoting (bioactive) compounds of food. In this study, “Obsidian” and “Triple Crown” blackberries (both Rubus hybrids) were cultivated organically and fertilized with either soy meal, fish emulsion/hydrolysate blend, or processed poultry litter fertilizers at a fixed rate. Fruits were hand-harvested three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Phenolic compounds have beneficial health-promoting properties and are regarded as the class of compounds mostly found in edible plants, fruits, and beverages among the phytochemicals [ 8 ]. They are effective in the treatments against several debilitating diseases such as cancer, diabetes, inflammation, pathogenic infections and aging, amongst others [ 9 , 10 ]. While some phenolics have demonstrated potential in the treatment and management of diabetes and its complications [ 11 ], an insight into deciphering the nature of interaction(s) with the implicated key enzymes is imperative to provide evidence-based data supporting their antidiabetic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds have beneficial health-promoting properties and are regarded as the class of compounds mostly found in edible plants, fruits, and beverages among the phytochemicals [ 8 ]. They are effective in the treatments against several debilitating diseases such as cancer, diabetes, inflammation, pathogenic infections and aging, amongst others [ 9 , 10 ]. While some phenolics have demonstrated potential in the treatment and management of diabetes and its complications [ 11 ], an insight into deciphering the nature of interaction(s) with the implicated key enzymes is imperative to provide evidence-based data supporting their antidiabetic potential.…”
Section: Introductionmentioning
confidence: 99%
“…A more localized production, as observed in this year, tends to generate lower sales prices, in addition to a short product offering period, hindering production flow. Considering a short post-harvest life, varying from 4 to 8 days depending on the cultivar (Cavender et al, 2019), production scheduling can greatly help to ensure good fruit prices.…”
Section: Resultsmentioning
confidence: 99%
“…This fact, added to its short post-harvest life generates a fruit that reaches market shelves with high prices. With promising potential and good prospects for commercialization, the fruit can be consumed fresh or used to produce a wide variety of products that can be offered on rural tourism routes and in free markets (Antunes & Hoffmann, 2012;Antunes & Raseira, 2004;Cavender et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies of the various chemical constituents may be related to harvest date, time, location, and year-to-year growing period (Sharp et al, 2014). Recent study conducted by Cavender et al (2019) reported that harvested period had a greatly effect to influence the variations of sugar contents. The amount of protein content in NPS at 7.04% indicated that it could be used as a protein supplement for muscle development and maintaining human health (Wakili et al, 2015).…”
Section: Discussionmentioning
confidence: 99%